Analysis of secondary phases segregated and precipitated in SnO2-based varistors - Parra, R.; Castro, M. S.; Varela, José Arana [UNESP] (Elsevier B.V., 2005)
Transmission and scanning electron microscopy techniques were used to study the heterogeneities found in the microstructure of (SnO2Co3O4Nb2O5Fe2O3)-Co-.-Nb-.-Fe-. and (SnO2ZnONb2O5FC2O3)-Zn-.-Nb-.-F-. varistors. Second phases encountered both inside the grains and ingrain boundary regions were identified using energy dispersive spectrometry and electron diffraction patterns. Through the electrical characterisation, the presence of iron oxide among the additives was determined to highlight the non-linear properties of the specimens. A discussion on the influence of second phases on the non-linear features of these systems is also addressed. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: electron microscopy; grain boundaries; microstructure-final; varistors; SnO2